Ultrasound-Guided Thermal Ablation of Thyroid Nodules: Technicalities Progress and Clinical Applications, Especially in Malignant Thyroid Nodules - Agyekum, Enock Adjei; Fu, Jian-hua; Xu, Fei-Ju; Ren, Yong-Zhen; Akortia, Debora; Chen, Qing; Qian, Xiao-Qin; Wang, Yuguo; Wang, Xian (Frontiers in Oncology, 2021)
Thyroid nodules are commonly encountered in health care practice. They are usually benign in nature, with few cases being malignant, and their detection has increased in the adult population with the help of ultrasonography. Thyroidectomy or surgery is the first-line treatment and traditional method for thyroid nodules; however, thyroidectomy leaves permanent scars and requires long-term use of levothyroxine after surgery, which makes patients more reticent to accept this treatment. Thermal ablation is a non-invasive techniques that have been employed in the treatment of benign thyroid and malignant thyroid nodules, and have been shown to be effective and safe. Several studies, including long-term, retrospective, and prospective studies, have investigated the use of ablation to treat benign thyroid nodules and malignant thyroid nodules, including papillary thyroid carcinoma. Here we review the recent progress in thermal ablation techniques for treating benign and malignant nodules, including their technicalities, clinical applications, pitfalls and limitations, and factors that could affect treatment outcomes. Finally, we summarize the advantages and disadvantages of thyroid ablation treatment, recurrence and metastatic situation and measures after thermal ablation. And we list the new progress about appliance in T1b and T2 stages of PTC.